2006
DOI: 10.1002/med.20099
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase inhibitors: A comparative QSAR study review and evaluation of new QSARs

Abstract: This paper contains a quantitative structure activity relationship (QSAR) study for lipoxygenase (LO) inhibitors. It reveals that in almost all cases, the clog P parameter plays an important part in the QSARs (linear or bilinear model). In some cases the steric factors such as the overall molar refractivity (CMR) or the substituents molar refractivity (MR) (linear or parabola) are important. Electronic effects are comparatively unimportant. The study shows that log P as calculated from the Clog P program is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
3
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 75 publications
2
54
3
8
Order By: Relevance
“…It is important to be noticed that the transformation of a3 to the bis-chalcone ether b3 led to a more potent derivative (IC 50 ¼ 56 lM). Lipophilicity was referred as an important physicochemical property for LOX inhibition 40 . This physicochemical property could explain the increase of anti-LOX activity in b3 (clog P values for a3 ¼ 3.66, whereas b3 ¼ 9.00).…”
Section: Biological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to be noticed that the transformation of a3 to the bis-chalcone ether b3 led to a more potent derivative (IC 50 ¼ 56 lM). Lipophilicity was referred as an important physicochemical property for LOX inhibition 40 . This physicochemical property could explain the increase of anti-LOX activity in b3 (clog P values for a3 ¼ 3.66, whereas b3 ¼ 9.00).…”
Section: Biological Evaluationmentioning
confidence: 99%
“…There is no universally accepted approach to evaluate the relative potency of different substances to cause LOX inhibition. However, most of the LOX inhibitors are antioxidants or free radical scavengers 40 . Herein, the results from the anti-lipid peroxidation activity studies support the anti-LOX activity for the bis-halcones b1-b4.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…This is in accordance with the finding of Curini et al 57 who have studied the antioxidant and LOX inhibitory activity of five natural prenyloxycarboxylic acids and showed that the most efficient LOX inhibitor (boropinic acid) is not the most active DPPH radical scavenger. Lipophilicity is referred 58 as an important physicochemical property for LOX inhibitors, and the above tested derivatives 7a and 7b seem to follow this concept (clog P 7b > clog P 7a, IC 50 7b > IC 50 7a).…”
Section: Biological Studiesmentioning
confidence: 92%
“…Lipophilicity is referred [47][48][49] as an important physichochemical property for lipoxygenase inhibition.…”
Section: Biological Studiesmentioning
confidence: 99%